Congenital Duplication of Small Intestine: Clinical Case - Elena S. Zastelo; Elvira N. Fedulova; Anna I. Gagarina; Tatyana V. Skochilova; Anatoly I. Khavkin (Вопросы современной педиатрии)
Background. Congenital duplication of small intestine is a complex disease in terms of early diagnosis due to the absence of specific clinical manifestations. Screening methods do not always help to reveal the lesion localization. Only special methods, such as contrastenhanced fluoroscopy, computed and magnetic resonance imaging, allow us to diagnosis gastrointestinal tract (GIT) malformation more precisely. Moreover, the lack of sufficient awareness about this pathology among primary care physicians also postpones diagnosis and, therefore, the timely correction of this congenital GIT malformation. Thus, our clinical case should help primary care physicians to increase alertness on congenital bowel anomaly. Clinical case description. This clinical case demonstrates that intestinal abnormality was suspected in utero at the first trimester of pregnancy according to ultrasound examination. Intestinal colics can be considered as the first clinical non-specific manifestation of congenital anomaly of small intestine in a child under the age of 1 year. Constipation, abdominal pain, and occasional pyretic fever were observed from the age of 2. Intestinal ultrasound has revealed changes, and radiological and magnetic resonance methods confirmed the presence of small intestine malformation. Conclusion. Screening ultrasound of an intrauterine child in the first trimester of pregnancy could force pediatricians to search congenital GIT anomalies despite its non-specific clinical signs. Imaging methods revealed the defect localization, while surgical intervention recovered it. It has prevented any possible complications and improved the patient’s quality of life.